Is protein-energy intake adequate during dialysis treatment in hemodialysis patients ? - Trudeke (G); Najoua Zanaki; Maryam Hdoudou; Peter J.M. Weijs (The Korean Society of Nephrology, 2012)
Protein-energy wasting (PEW) is a strong predictor of mortality in patients with chronic kidney disease. Although PEW is caused by non nutritional conditions, research indicates that nutritional support that targets adequate protein intake improves outcome. During dialysis therapy in-centre meals and snacks are provided. The question is whether these meals provide adequate protein and energy intake considering external (at home) consumed meals? Indirect calorimetry and physical activity Level (PAL) were performed to provide daily energy needs. Three day food record was performed for 2 dialysis days and 1 non dialysis day. Statistical analysis was done using SPSS19, paired T-test was used to detect significant differences (p<0.05). Mean and standard deviations are given. In the VU University Medical Centre 20 hemodialysis patients (12 men), mean age 58±3 year, BMI (kg/m2) 26±6 were enrolled. Protein intake was 82% of protein requirements (68+21 vs 83+12 g/d, p<0.001). Energy intake was 87% of energy requirements (1636+483 vs 1878±244 kcal/d, p<0.001). Protein intake on dialysis days was 72±19 vs 65±29 g/d on non-dialysis days (p<0.142). Energy intake on dialysis days was 1786±486 vs 1570±609 kcal/d on non-dialysis days (p<0.031). Dinner or lunch provided 39% of the daily energy needs, which is adequate according to a national guideline; and 35% of daily protein needs, which is lower than healthy Dutch adults. Conclusion: Protein and energy intake of hemodialysis patients is lower than their daily needs. On non dialysis days intake is even lower than on dialysis days. The meals consumed during dialysis treatment contain enough energy but not enough protein to meet requirements.